New Perspectives on the II CIAM onwards: How Does Housing Build Cities? - Porotto, Alessandro (2019)
Far from nostalgically celebrate the 90th anniversary of the second CIAM, which indeed opened in October 1929 in Frankfurt, the present issue is intended as collective work, a springboard which aims to widen the debate over housing experiences beyond geographical and temporal frameworks. The focus of that event, the Existenzminimum, has often been cited as representing a fundamental contribution to the rational design of the modern dwelling. But the debates during that event went beyond the definition of this concept, because demonstrated, on the one hand, how the responsibility of architects would imply the resolution of multiple technical aspects, starting from the typological concern stretching towards the town planning aspects, and on the other hand, the calling to develop a multifaceted intellectual vision of society. Though the title selected for the present issue, namely ‘Housing Builds Cities’, denotes the different scales of the project, the aim is to achieve a something more. First and foremost, the objective is not strictly confined to a historical understanding of facts around the 1929 congress. Today a critically objective approach is useful to examine past contributions and, if applicable, their actualization. Secondly, this special issue intends to address the CIAMs’ theoretical and architectural legacy. The hypothesis on their interpretation suggests that these are still topical issues today. The issue comprises fourteen articles which investigate, through different applied methodologies, the years from the first steps of the CIAMs to the 1929 aftermath, analyze the post-war production and explore many case-studies, of which some are also geographically far from a Euro-centric vision as well as contemporary realities.